PEMILIHAN UMUM SERENTAK DAPAT MEMPERKUAT SISTEM PRESIDENSIAL - Barhamudin, Barhamudin (Faculty of Law, University of Palembang, 2018)
The purpose of this research is to find out whether general elections simultaneously have an influence on strengthening presidential systems. To find out the implications of simultaneous elections on elections in Indonesia. The research method in this study uses a normative juridical approach used to study or analyze secondary data in the form of legal materials, especially primary legal materials and secondary legal materials. Primary legal material is the 1945 Constitution of the Republic of Indonesia, Law Number 7 of 2017 concerning General Elections, Decision of the Constitutional Court Number 14 / PUU-XI / 2013 etc. Secondary legal materials are those that provide explanations and interpretations of sources of primary legal materials such as law books, legal journals, and others. Tertiary legal materials are legal materials that provide guidance or explanation of primary and secondary legal materials such as legal dictionaries, encyclopedias, and related documents. The results of the study were argued that the holding of elections simultaneously with the plurality system itself actually tended to produce few presidential candidates. When presidential elections the supporters of candidates in this system tend to ignore candidates who are not competitive (non-viable) so they can focus on the top two candidates. This encouraged a coalition process between parties from the start because there was only one election round. The party that should submit its own candidate but the candidate is less competitive tends to drop the candidate and endorse one of the two most competitive candidates. The plurality system, if implemented separately from the legislative elections, the parties in the legislative elections do not need to think about the influence of the presidential election. This plurality mechanism affects parties when carried out simultaneously with legislative elections. The parties tend to nominate one of the two most competitive candidates, and lead to gathering support for the legislative parties in the two candidates. When one of the candidates wins the presidential election, then support for the president in the legislature tends to be the majority or close to the majority. The combination of the presidential plurality election system carried out simultaneously with legislative elections is the most likely to help strengthen multi-party presidential systems. Thus the simultaneous implementation of elections will strengthen the presidential system in which the President and Vice-President are elected to gain strong legitimacy from the people, in order to realize the effectiveness of government and also the support base of the DPR.